A Stylistic Analysis of Hey Jude by The Beatles: Linguistic and Literary Perspectives on Musical Expression - Errando Varel; Rofnal Samangilailai; Davis Timothy Humala Hutapea; Alvin Afian; Rahmadsyah Rangkuti (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
Hey Jude by The Beatles is one of the most influential songs in modern music, known for its emotional depth and universal appeal. This study aims to analyze the stylistic characteristics of the song using a linguistic and literary stylistic approach. A qualitative descriptive method is employed to examine lexical choices, syntactic structures, phonetic devices, and discourse organization in the lyrics. The findings reveal that the song relies heavily on repetition, imperative sentence structures, and phonetic patterns to create a powerful and memorable emotional effect. The extended coda and rhythmic consistency further enhance its impact. The analysis concludes that Hey Jude employs stylistic techniques that reinforce its themes of encouragement, resilience, and human connection, making it a timeless piece in musical and linguistic expression.